Cast iron filings-based model for observation of nitrate reduction in corroded system. Issue 41 (1st September 2016) - Laskowski, T.; Sroka, M.; Olejnik, A.; Biernacki, W.; Nawrocki, J.
Abstract: Applicability of cast iron filings-based model for a study of nitrate reduction phenomena in water distribution networks is shown in this paper. The experiments were conducted both on 100-m long corroded cast iron pipe and on a laboratory model with cast iron filings. Additionally, the fate of nitrate was monitored at far ends of two real, large distribution systems. Results from all these systems show that nitrate reduction occurs mainly during water stagnation and is an effect of both biotic and abiotic processes. Decreasing concentration of nitrate may be accompanied by ammonia formation, mainly in fresh pipes. However, the changes of nitrogen concentration are not balanced. It is suggested that the lack of stoichiometry is related to denitrification leading to N2 formation. Along with the passing of time, the share of denitrification rises. Chemical disinfection does not prevent the biological denitrification in corroded water supply system. The results prove that the nitrate takes part in corrosion exclusively on fresh, unused surface of cast iron. The decrease in nitrate concentration is mainly connected with biological denitrification, which occurs due to the considerable extent during stagnation of water in the distribution system. The observation of large distribution systems proves that under flow conditions, no nitrate reduction occurs.